Validation of the Safer Opioid Prescribing Evaluation Tool (SOPET) for Assessing Adherence to the Centers for Disease Control Opioid Prescribing Guidelines. Issue 12 (22nd May 2020) - Navis, Allison; George, Mary-Catherine; Nmashie, Alexandra; Hoang, Ethan; Cedillo, Gabriela; Robinson-Papp, Jessica
Abstract: Objective: In response to the opioid epidemic, the Centers for Disease Control and Prevention issued guidelines (CDCG) in 2016 for the prescription of opioids for chronic pain. To facilitate research into whether CDCG implementation will lead to reductions in opioid prescribing and improved patient safety, we sought to validate a tool that quantifies CDCG adherence based on clinical documentation. Design: The Safe Opioid Prescribing Evaluation Tool (SOPET) was developed in four phases as part of a study to improve the implementation of the CDCG in the clinical setting. Four raters with varying levels of clinical experience and expertise were trained to use the SOPET and then used it to evaluate 21 baseline patient encounters. Intraclass correlation coefficient (ICC) estimates and their 95% confident intervals (CIs) were calculated for the total SOPET score based on a mean-rating (k = 4), absolute-agreement, two-way random-effects model. For intrarater reliability, two-way mixed-effect models were used. Results: Inter-rater reliability was good, with an average-measures ICC of 0.82 (95% CI = 0.63–0.92). Intrarater reliability was excellent for the three raters, who were MDs, with average-measures ICCs as follows: 0.92 (95% CI = 0.81–0.97), 0.97 (95% CI = 0.92–0.99), 0.99 (95% CI = 0.99–0.99). However, the intrarater reliability for the non-MD rater was lower 0.69 (95% CI = 0.22–0.88). Conclusions: Overall, the SOPET is useful for evaluating implementation of the CDCG in clinical documentation. It is an important first step in the design of future studies assessing whether adherence to the CDCG improves patient safety outcomes.